Manfaat Motivasi Kerja Dibidang Usaha Kerupuk - Jaenudin J; Muhamad Septiaraya Latif; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Our goal of visiting Umkm's place is to expand existing sales in our city, namely Karawang and also improve culture. Work motivation is a driving force in a person to behave and work diligently in accordance with the duties and obligations that have been given to him. The decline in work motivation for MSME actors in Belendung village can be caused by several factors, starting from the Covid-19 pandemic which has reduced sales productivity to no there was a month's worth of productivity, as well as an increase and scarcity of materials to make products. The methods used in this service are interviews and observation. Interviews were conducted in order to obtain information directly to explain a matter or situation and conditions that occur in SMEs. While observations are made with the aim of drawing conclusions by direct observation. Based on the research conducted, the result is that there is a decrease in work motivation for MSME actors in Belendung village, this is caused by problems that occur without any effort to increase work motivation so that they can work optimally.